The Influence of Learning Community On Pedagogical Competence Of Public Elementary School Teachers - Santoso Wuryandoko; Maryanto Maryanto; Ghufron Abdullah (Universitas Negeri Semarang, 2025)
Teacher pedagogical competence is their ability to manage learning comprehensively, including understanding students; planning; implementing; evaluating; utilizing technology; and developing student potential to achieve optimal learning outcomes. Teacher pedagogical competence is influenced by internal and external factors, one of which is participation in a learning community. This study aims to determine and analyze the influence of learning communities on the pedagogical competence of elementary school teachers in Japah District, Blora Regency. This study has a novelty by integrating learning communities with teacher pedagogical competence, which has not been widely studied in elementary school teachers in Japah District, Blora Regency, thus providing a more comprehensive understanding of the factors that influence teacher pedagogical competence in elementary schools. This study uses a quantitative method with data collection through distributing questionnaires with a sample of 130 respondents. The results of the study showed that learning communities have a positive and significant effect on teacher pedagogical competence. From the results of the study, it can be concluded that the learning community has a positive effect with a correlation coefficient of 0.364 or 36.4% on teacher pedagogical competence and the remaining 63.6% is influenced by other factors that were not studied. The learning community is the most dominant variable with an effective contribution (SE) of 14.6%.